2021
DOI: 10.1007/s40615-021-00988-8
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities and COVID-19: the Social Context

Abstract: The coronavirus continues to take a devastating toll on the population of the USA. But that toll is not identical across all segments of the population. Specifically, Black citizens are more likely than their White counterparts to experience the dislocations associated with the coronavirus. Nor is the extent of racial differences fully known, given limitations to the testing, hospitalization, and other data currently compiled. What does emerge, however, is an understanding that the reported outcomes reflect so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…In the first half of 2020, life expectancy in the USA dropped 2.7 years for Black people and 1.9 years for Latinx people, compared to dropping only 0.8 years for Whites [ 42 ]. These racial/ethnic inequities are due, in large part, to historical and present-day structural racism (public and institutional policies and practices that create or reinforce racial inequity) [ 43 ]. Structural racism, for example, created segregated neighborhoods where deleterious social determinants of health have given rise to the illnesses that make people vulnerable to serious COVID-19 disease [ 44 ] and is associated with greater incidence and mortality for Black and Latinx residents [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the first half of 2020, life expectancy in the USA dropped 2.7 years for Black people and 1.9 years for Latinx people, compared to dropping only 0.8 years for Whites [ 42 ]. These racial/ethnic inequities are due, in large part, to historical and present-day structural racism (public and institutional policies and practices that create or reinforce racial inequity) [ 43 ]. Structural racism, for example, created segregated neighborhoods where deleterious social determinants of health have given rise to the illnesses that make people vulnerable to serious COVID-19 disease [ 44 ] and is associated with greater incidence and mortality for Black and Latinx residents [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within this history was the discovery of the U.S. Public Health Service Syphilis Study at Tuskegee, a major bioethical failure to the core principles of public health. What has emerged from its legacy is another example of historical trauma, community harm, and the systemic disenfranchisement of Black, Indigenous, and People of Color (BIPOC) communities, which has fostered mistrust in our public health infrastructure and has woven a complex web of confusion and misinformation encumbering decisions to engage in protective behaviors to prevent and treat COVID-19 [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Koh [16] indicated that "COVID-19 is the first new occupational disease to be described in this decade." Moreover, focusing on factors beyond pre-existing health conditions and behavioral risk factors [17][18][19] sheds light on structural factors beyond individual behavior that impact the risk of COVID-19. The high racial disparities in COVID-19-related deaths in a younger population (aged ≤ 65 years compared to aged > 65 years) [20] also provides further justification for exploring work-related factors.…”
mentioning
confidence: 99%